Clinical Efficacy and Safety of Propranolol in the Prevention and Treatment of Retinopathy of Prematurity: A Meta-Analysis of Randomized Controlled Trials - Kong, Haibo B.; Zheng, Guoyuan Y.; He, Baomei M.; Zhang, Ying; Zhou, Qin (Frontiers in Pediatrics, 2021)
Objective: To perform a meta-analysis of randomized controlled trials verifying clinical efficacy and safety of propranolol in pre-term newborns with retinopathy of prematurity (ROP). Methods: We searched the literature databases (Pubmed, Embase, The Cochrane Library, Web of Science, CNKI, WanFang, VIP, CBM) for publications before August 10, 2020, and the World Health Organization's International Clinical Trials Registry and ClinicalTrials.gov for ongoing trials. Randomized controlled trials (RCTs) of propranolol for the prevention or treatment of ROP were included. The quality of the included studies was primarily assessed by the RCT tool of the Cochrane Collaboration. The included studies were quantified using a meta-analysis of relative risk (RR) estimated with a random effect model. Results: Our original search identified 171 articles, and five studies met our criteria. A meta-analysis was performed that showed that infants orally treated with propranolol had a decreased risk of disease progression: stage progression had an RR = 0.65 [95% confidence interval (CI), 0.47–0.88]), plus disease had an RR = 0.43 [95% CI, 0.22–0.82]. The demands for additional treatments had similar protective results: laser photocoagulations had an RR = 0.55 [95% CI, 0.35–0.86]), and intravitreal injection of anti-vascular endothelial growth factor had an RR = 0.45 [95% CI, 0.22–0.90]). The oral administration of propranolol was associated with an increased risk of adverse events (RR = 2.01 [95% CI, 1.02–3.97]). High-risk adverse events included bradycardia, hypotension, not gaining enough weight, bronchospasm, hypoglycemia, apnea, and increasing ventilator need. Subgroup analysis of ROP phases and stages found that the risk in stage 2 ROP of the second phase and the individual risk factors (stage progression, RR = 0.42 [95% CI, 0.27–0.65]; plus disease, RR = 0.40 [95% CI, 0.17–0.93]; laser photocoagulation, RR = 0.31 [95% CI, 0.14–0.68]) have statistically significant differences compared with other phases and stages. Conclusions: Pre-term newborns with ROP, especially in stage 2 ROP of the second phase, who were orally given propranolol have a reduced risk of disease progression and demand for additional treatments, but the safety needs more attention.